Serum prolactin and gonadotropin levels in women with infertility in Bangladesh (IMC Journal of Medical Science, 2018)
Background and objectives: Infertility is a global health problem including Bangladesh. Altered prolactin, follicle (FSH) and luteinizing hormones (LH) levels have been implicated as a cause of infertility. The present study was undertaken to find out the serum prolactin and gonadotropin levels in women with primary and secondary infertility.Methods: The study involved a total of 100 women of which 50 had primary (Group A) and another 50 had secondary (Group B) infertility. Fifty fertile age-matched women were included as control (Group C). All the study participants were selected from women attending the infertility unit of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Serum prolactin, FSH and LH hormones were measured by radioimmunoassay with blood collected on the 2nd day of menstrual cycle.Results: The mean serum prolactin level was significantly higher (